Pelatihan Jualan Online untuk Meningkatkan Wawasan tentang Pemanfaatan Internet bagi Masyarakat Pemulung di Wilayah Makam Rangkah Surabaya - Barry Nuqoba; Faried Effendy; Army Justitia; Indah Werdiningsih (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2021)
Most of residents in Rangkah cemetery area Surabaya have low economic level. Majority of the residents work as scavengers. The Surabaya City Government has provided assistance in the form of free internet for residents, but it has not been used optimally for improving their wealth due to lack of knowledge and skills to utilize internet as an alternative source of income. Selling online is the activity of selling goods/services using the internet. One of the advantages of selling online is that it does not require a large initial capital. The main purpose of this community service is to provide online sales training using social media Facebook as an alternative source of income to improve the economy of the scavenger community. This community service activity was attended by 31 children who are scavengers. The results of the measurement of the success of the training showed a significant number, only 20% of participants able to corectly answer at least half of the questions (pre-test), and after the training, 94% of participants able to correctly answer of at least 7 questions (post-test)